2016
DOI: 10.4172/2378-5756.1000373
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Common Mental Disorders and Associated Factors among Residents of Jimma Town, South West Ethiopia

Abstract: Journal of Psychiatry AbstractBackground: Common mental disorders such as anxiety, depression and unexplained somatic symptoms and substance use disorders such as alcohol, khat and cigarette contributes to disability and distress to the population impeding productivity and affecting societal wellbeing. Recognizing this, the current study was conducted to be one input for policy maker's efforts in reforming mental health care among the community in our country.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
31
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(51 citation statements)
references
References 15 publications
16
31
4
Order By: Relevance
“…Majority of the CMD cases in our study were females when compared to their male counterparts. This is similar to findings from other studies done in Ethiopia and Malawi [ 27 – 29 ]. The reason for this could be as a result of gender disadvantages like social burden and maternity issues.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Majority of the CMD cases in our study were females when compared to their male counterparts. This is similar to findings from other studies done in Ethiopia and Malawi [ 27 – 29 ]. The reason for this could be as a result of gender disadvantages like social burden and maternity issues.…”
Section: Discussionsupporting
confidence: 93%
“…As this study was conducted in PHC settings, where respondents came chiefly to address their underlying health problems, over-reported symptoms of CMDs may had pathologic origin related to it and hence might have contributed to high rate of prevalence. The result from this study appeared to be lower when compared to prevalence of two towns in Ethiopia, 33.6% in Jimma and 32.4% in Kombolcha [ 27 , 28 ]. According to the WHO reports from 14 countries worldwide, the prevalence of CMD in PHC settings is 24% [ 24 ], which is almost similar to the finding in this study.…”
Section: Discussioncontrasting
confidence: 72%
“…The psychosocial effect of khat chewing depends on its capacity to lead to dependency or addiction and to the specific physical and behavioral effect including socio economic effect for individuals might be lead to common mental disorders. This finding is supported by other studies (21,26,33) Family history of mental illness were significantly associated with common mental disorders.Parental history of mental illnessmight increase the risk of CMDs in the offspring through different reasons like transmission of genetic factors.This finding is similar with studies of other part of Ethiopia (18)(19)(20)30).…”
Section: Factors Associated With Common Mental Disorderssupporting
confidence: 88%
“…To determine the prevalence of CMD, both studies followed a community based cross sectional study design and used a Self-Reporting Questionnaire (SRQ). The results of both studies indicated that there is a high prevalence of CMD among different groups of the society [ 42 ].…”
Section: Definition Of Mental Health and The Major Mental Illness:mentioning
confidence: 99%